Determination of Base and Non-Base Sectors in Bangka Regency with Location Quotient Analysis Method - Julia, Julia; Saputra, Darman; Herdiyanti (Indonesian Journal of Social Science Research, 2021)
Identification of basic sectors and sub-sectors is one of the stages for planning the expansion of strategic areas as centers of economic growth. Location Quotient analysis is needed to find out how far the level of interest in the economic sector in Bangka Regency is in utilizing the base sector or superior sector. The variable used to calculate the basic economy is from local GDP an activity that is focused on activities within the local economic structure. Gross Domestic Product (GDP) is an important indicator to understand economic conditions, especially in Bangka Regency in a certain period, both based on current prices and constant prices. The data collection process was carried out using a secondary data survey by taking data on land area and production of biopharmaceutical plant commodities, vegetable crops, rice or secondary crops, plantations and fisheries. By calculating the location quotient analysis, the base sector is obtained in every sub-district in Bangka Regency so that this result is expected to determine the investment can be carried out on target.